KEBEBASAN BERAGAMA DALAM ISLAM - Wijayanti, Tri Yuliana (JURNAL AL-AQIDAH, 2019)
Every human being is free to choose a religion according to his religious experience and in accordance with his personal beliefs. Freedom of religion also includes the situation conducive for people to choose religion (according to his) and to his religion without restriction and coercion from any party. The challenges of today's religious life in contrast to the issue of religious freedom and the fact of religious plurality. Religious pluralism urged all religions to think practically how to get along with other religious and theological interpret the meaning of the presence of religion and belief.